Auxin-Dependent Cell Elongation During the Shade Avoidance Response - Ma, Lin; Li, Gang (Frontiers in Plant Science, 2019)
Plant uses multiple photoreceptors and downstream components to rapidly respond to dynamic changes in environmental light. Under shade conditions, many species exhibit shade avoidance responses that promote stem and petiole elongation, thus helping plants reach the sunlight. In the last few years, the regulatory molecular mechanisms by which plants respond to shade signals have been intensively studied. This review discusses the regulatory mechanisms underlying auxin-mediated cell elongation in the shade avoidance responses. In the early response to shade signals, auxin biosynthesis, transport, and sensitivity are all rapidly activated, thus promoting cell elongation of the hypocotyls and other organs. Under prolonged shade, increased auxin sensitivity—rather than increased auxin biosynthesis—plays a major role in cell elongation. In addition, we discuss the interaction network of photoreceptors and Phytochrome-Interacting Factors, and the antagonistic regulation of Auxin/Indole Acetic Acid proteins by auxin and light. This review provides perspectives to reframe how we think about shade responses in the natural environment.